SOME BERBER ETYMOLOGIES X - Takács, Gábor (Lingua Posnaniensis, 2013)
My series “Some Berber Etymologies” is to gradually reveal the still unknown immense Afro-Asiatic heritage in the Berber lexical stock. The first part with some miscellaneous Berber etymologies was published back in 1996. Recently, I continued the series according to initial root consonants1 in course of my research for the volumes of the Etymological Dictionary of Egyptian (abbreviated as EDE, Leiden, since 1999, Brill)2 with a much more extensive lexicographical apparatus on the cognate Afro- Asiatic daughter languages. As for the present part, it greatly exploits the results of my ongoing work for the the fourth volume of EDE (analyzining the Eg. lexical stock with initial n-). The present part contains etymologies of Berber roots with initial *n- followed by sibilants. The numeration of the entries continues that of the preceding parts of this series. In order to spare room, I quote those well-attested and widespread lexical roots that appear common Berber, only through a few illustrative examples. The underlying regular consonant correspondences between Berber vs. Afro-Asiatic agree with those established by the Russian team of I.M. Diakonoff and summarized by A.Ju. MILITAREV: (1991, 242-243).